Two plastidic glycolate/glycerate translocator 1 isoforms function together to transport photorespiratory glycolate and glycerate in rice chloroplasts. (23rd January 2021) - Cui, Lili; Zhang, Chuanling; Li, Zhichao; Xian, Tuxiu; Wang, Limin; Zhang, Zhisheng; Zhu, Guohui; Peng, Xinxiang
Abstract : Two chloroplastic transporters work together as a complex to transport glycolate/glycerate and are required for photorespiratory metabolism and plant growth. Abstract: The photorespiratory pathway is highly compartmentalized. As such, metabolite shuttles between organelles are critical to ensure efficient photorespiratory carbon flux. Arabidopsis plastidic glycolate/glycerate translocator 1 (PLGG1) has been reported as a key chloroplastic glycolate/glycerate transporter. Two homologous genes, OsPLGG1a and OsPLGG1b, have been identified in the rice genome, although their distinct functions and relationships remain unknown. Herein, our analysis of exogenous expression in oocytes and yeast shows that both OsPLGG1a and OsPLGG1b have the ability to transport glycolate and glycerate. Furthermore, we demonstrate in planta that the perturbation of OsPLGG1a or OsPLGG1b expression leads to extensive accumulation of photorespiratory metabolites, especially glycolate and glycerate. Under ambient CO2 conditions, loss-of-function osplgg1a or osplgg1b mutant plants exhibited significant decreases in photosynthesis efficiency, starch accumulation, plant height, and crop productivity. These morphological defects were almost entirely recovered when the mutant plants were grown under elevated CO2 conditions. In contrast to osplgg1a, osplgg1b mutant alleles produced a mild photorespiratory phenotype and had reduced accumulation of photorespiratory metabolites. Subcellular localization analysis showed that OsPLGG1a and OsPLGG1b are located in the inner and outer membranes of the chloroplast envelope, respectively. In vitro and in vivo experiments revealed that OsPLGG1a and OsPLGG1b have a direct interaction. Our results indicate that both OsPLGG1a and OsPLGG1b are chloroplastic glycolate/glycerate transporters required for photorespiratory metabolism and plant growth, and that they may function as a singular complex.